Broadcasting Scheme for Real Time Video in mobile Adhoc Network - et. al., Dr. Kamal Upreti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A video on real time system is a multimedia platform that is used by the user to take pleasure in their time and for providing them to select any video. Moreover, no matter what is the time and what is the place suitable for the huge video database storage space in the cloud server. With the increasing demand of video on system major challenges faced are to lessen the buffer space, client waiting time and required bandwidth. To overcome these challenges many videos on demand techniques are developed. In these techniques, there is the problem of many numbers of channels. In this manuscript the problem of broadcasting in mobile ad hoc network is considered. A proposal is designed in broadcasting protocol, which evaluates the performance using the periodic broadcast technique. This technique provides less client waiting time and less buffers requirement than other techniques.